ORGANIZATIONAL MECHANISM OF MANAGING THE DEVELOPMENT OF SOCIAL ENTREPRENEURSHIP IN UZBEKISTAN - Shukhrat ogli, Narzullaev Elmurod (International Journal of Business, Law, and Education, 2025)
The main objective of this study is analyzing the capability of improving and developing organizational methodological mechanism of managing the development of social entrepreneurship in Uzbekistan. The theoretical basis of the scale is supported by empirical research in the social sector. On other hand, finding out both strengths and weaknesses on managing and developing environmental social entrepreneurship in our country also was our main aim in this article.